Combined Surgical Technique of Hyperselective and Partial Motor Neurectomies for Spastic Equinus, Equinovarus, and Claw Toe Deformities - Kitty Y. Wu, MD; Paula A. Pino, MD; Daniel B. Ryssman, MD; Peter C. Rhee, DO, MSc (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Patients with spastic equinus, equinovarus, and claw toe deformities can experience marked pain and functional limitations in the ability to weight-bear comfortably, ambulate efficiently, or mobilize independently. Seen in 80% of patients with cerebral palsy and 18% of patients with stroke (1, 2), the spastic foot and ankle deformities, and its secondary sequelae of static joint contractures, osseous changes, and chronic pain, are unfortunately common. Methods:. Adult and pediatric patients undergoing combined hyperselective and selective partial motor neurectomies for varus or claw toe deformities were reviewed. Patient demographics and complications were recorded. Pre- and postoperative Modified Ashworth Scale scores were compared. Results:. Twenty-three patients (16 adults and seven pediatric) met inclusion criteria and were included in analysis. At early 6-month follow-up, the mean preoperative Modified Ashworth Score of 2.8 in adult patients and 3.0 in pediatric patients decreased to 0.6 postoperatively. Complications in three adult patients included one patient with temporary dysesthesias to the plantar foot, one with a popliteal abscess requiring incision and drainage, and one superficial wound dehiscence that was managed conservatively. Conclusions:. A combined technique of hyperselective and partial motor neurectomies are effective in decreasing tone in the correction of spastic foot and ankle deformities in both adult and pediatric patients in short-term 6-month follow-up.